Letter to Jane Tolmach from John B. Connally, Secretary of the Navy - John B. Connally:::::: (1961)
A letter to Jane Tolmach from John B. Connally, Secretary of the Navy, stating that he cannot meet with her in regards to her concerns about the film "Communism on the Map."